Decomposition and attribution analysis of the coupled evolution characteristics of groundwater and land subsidence in the Beijing-Tianjin-Hebei Plain - Yongkang Wang; Huili Gong; Chaofan Zhou; Qin Wang; Haotong Wang; Jincai Zhang (Journal of Hydrology: Regional Studies)
Study region: This study investigated the relationship between groundwater storage and land subsidence and analyzed the potential causes of these variations in the Beijing-Tianjin-Hebei Plain from 2018 to 2022. Study focus: Independent Component Analysis (ICA) was applied to separate signals from Interferometric Synthetic Aperture Radar (InSAR) surface deformation data and Gravity Recovery and Climate Experiment (GRACE) and GRACE-Follow On (GRACE-FO) groundwater storage anomalies. A spatiotemporal feature coupling analysis was then conducted on the periodic and trend components. The CNN-LSTM-attention neural network further quantified the drivers of groundwater changes in the trending subsidence area. New hydrological insights for the region: (1) periodic components showed a strong positive correlation (cross-correlation coefficient = 0.73, with land subsidence lagging behind groundwater storage changes by 1 month) and a 5–6 month delayed response to precipitation, with high-score areas clustered in the precipitation-rich eastern and southern BTHP. (2) The trend components revealed synchronized declines (2018–2021), followed by rebounds, with groundwater recovery outpacing subsidence mitigation. High-score zones were aligned with regions of intense groundwater extraction (e.g., the southern BTHP). (3) In the trending subsidence area, CNN-LSTM-attention model achieved higher accuracy (test set R²: 0.54 vs −0.99, RMSE: 13.11 mm vs 43.12 mm) using reconstructed groundwater signals, confirming precipitation and anthropogenic extraction as significant contributing factors. This study provides a reference for exploring the relationship between changes in groundwater reserves and land subsidence.